Soil Flooding Tolerance in Lentil at Vegetative Stage (Progressive Agriculture, 2013)
The experiment compared the relative tolerance of some advanced lines and a variety of lentil viz. BD3859, BD3905, BD3867, ILL5087, ILL5133 and BINAmasur1 (variety) to soil flooding. The growth rates of the genotypes considerably reduced when flooding imposed at vegetative stage. However, the genotypes responded differently to flooding onward during recovery period. Leaf and roots showed highly vulnerable to flooding. Flooding promoted extensive leaf senescence and desiccation. Flooding induced damaging of root system was highly striking, despite there existed remarkable recoveries in some genotypes. The adverse effect of flooding was less pronounced on stem than other plant components. However, shoot growth reduction was 76-86% relative to control. Relative growth rate (RGR) of most plant components showed negative rate during flooding, but it varied from negative to positive during recovery period. Considering total plant biomass, flooding tolerance (FT) indices indicated that BINAmasur1 and BD3859 had comparatively better degree of tolerance to excess water. In contrast, ILL5133 and ILL5087 were susceptible to flooding for having negative FT indices.DOI: http://dx.doi.org/10.3329/pa.v18i2.17460 Progress. Agric. 18(2): 17 - 24, 2007